Faktor yang Mempengaruhi Mood Belajar Piano Siswa Christina Music Course Tarutung - Sitorus, Christina Harianti; Purba, Mauly (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2024)
This study aims to analyze the factors that influence the piano learning mood of Christina Music Course Tarutung students. This research is a type of qualitative research by observing artistic phenomena, especially regarding the factors that influence the Piano Learning Mood of Christina Music Course Tarutung Students. Data collection techniques using interviews and observation. Data analysis techniques use data reduction, data presentation and drawing conclusions. This research was carried out at Christina Music Course Tarutung. To be able to play the piano, a person must understand basic music theory and understand the basic techniques of playing music. However, this is not only related to the theory of playing the piano, but the student's piano learning mood also greatly determines success in learning the piano. Mood has a positive and negative influence on student learning depending on how students respond to factors that influence mood. Students at CMC Tarutung feel that there are many factors that determine their mood, one of which is activities outside of the course which are quite tiring which has an impact on their mood.